2019
DOI: 10.29252/jhsme.6.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spiritual Group Counseling on the Psychological Well-Being of Girls from Divorced Families

Abstract: Background and Objectives: Divorce is a stressful life event both for parents and children. Nowadays, an increase in the divorce rate is one of the major problems and concerns in many countries of the world, especially in Iran. Divorce can be a deterrent factor in the personal growth and development of the children from broken families. This study aimed to develop a groupcounseling model based on spirituality to boost psychological well-being in girls from divorced families. Methods: This experimental study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In other words, spiritualreligious interventions can reduce anxiety and depression in female adolescents. Safara et al in their study showed that spiritual interventions can improve psychological well-being in female adolescents, which is consistent with the findings of the present research (19). Furthermore, Weber et al have shown that spiritual and religious beliefs and practices can promote mental health (28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, spiritualreligious interventions can reduce anxiety and depression in female adolescents. Safara et al in their study showed that spiritual interventions can improve psychological well-being in female adolescents, which is consistent with the findings of the present research (19). Furthermore, Weber et al have shown that spiritual and religious beliefs and practices can promote mental health (28).…”
Section: Discussionsupporting
confidence: 91%
“…According to previous studies, spirituality and religion can strengthen a person against the difficulties and adversities of life (17,18). Safara et al in their study showed that spirituality can improve one's mental health (19). Furthermore, spiritualityand religion-based practices can empower people in the face of adversities and lifethreatening diseases (20).…”
Section: Introductionmentioning
confidence: 99%
“…One example is Ash-Sha'rani, a sixteenth-century Sufi writer, who explains this seven-fold zikr in the following way (quoted in Schimmel, 1975): "dhikr al-lisan, with the tongue; dhikr an-nafs, which is not audible but consists of inner movement and feeling; dhikr al-qalb, with the heart, when the heart contemplates God's beauty and majesty in its inner recesses; dhikr ar-ruh, when the meditating mystic perceives the lights of the attributes; dhikr as-sirr, in the innermost heart, when divine mysteries are revealed; dhikr al-khafiy, the secret recollection, which means the vision of the light of the beauty of essential unity; and, finally, the dhikr akhfa al-khafi, the most secret of secret, which is the vision of the Reality of Absolute Truth (haqq al-yaqin)". Moving forward, numerous studies have been conducted on the usefulness of zikr meditation, being the exact opposite to the stress responses, to potentiate stress reduction, and improve physical and psychological well-being (Safara et al, 2019;Sulistyawati & Probosuseno, 2019;Rochdiat et al, 2019). Other studies have found that mindfulness meditation is associated with nature connectedness (Unsworth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%